A Suicide Monitoring and Crisis Intervention Strategy Based on Knowledge Graph Technology for “Tree Hole” Microblog Users in China - Yang, Bing Xiang; Xia, Lin; Liu, Lianzhong; Nie, Wentao; Liu, Qian; Li, Xin Yi; Ao, Meng Qin; Wang, Xiao Qin; Xie, Ya Dian; Liu, Zhongchun; Huang, Yi Jia; Huang, Zhisheng; et al. (Frontiers in Psychology, 2021)
“Zou Fan” is currently the largest “tree hole” on Weibo, where people having suicidal ideation often express their thoughts and use this channel to seek support. Therefore, early suicide monitoring and timely crisis intervention based on artificial intelligence technology are needed for this social media user group. This research was based on the knowledge graph technology, whereby “Tree Hole Intelligent Agent” (i.e., Artificial Intelligence Program) was used to identify “Zou Fan Tree Hole” users at high risk for suicide, and then, the “Tree Hole Action” carried out proactive suicide crisis intervention with them. The “Tree Hole Action” has temporarily prevented 3,629 potential suicides. The “Tree Hole Action” plays a significant role in suicide risk monitoring and crisis intervention for social media users and has been seen to have an important social impact.